2012
DOI: 10.1002/jmv.23336
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and molecular epidemiology of hepatitis B and hepatitis delta virus in pregnant women and in patients in Mauritania

Abstract: No recent data are available on hepatitis B virus (HBV) and hepatitis Delta virus (HDV) prevalence in Mauritania. One thousand twenty pregnant women and 946 patients visiting for routine checkups were screened for HBV and HDV infection. Demographic, epidemiological, ethnic, clinical, and biological data were recorded. HBV and HDV genotypes were determined by sequencing and phylogenetic analyses. In the pregnant women and patients cohorts, respectively, the prevalence of HBsAg (10.7% and 18.3%) and anti‐HBcAb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
64
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 39 publications
15
64
6
Order By: Relevance
“…Medical and surgical risk factors such as surgical procedures, home delivery, dental procedures, and history of jaundice were all found not to be significant [24,30,39,100,101].…”
Section: Medical or Surgical Risk Factorsmentioning
confidence: 81%
See 3 more Smart Citations
“…Medical and surgical risk factors such as surgical procedures, home delivery, dental procedures, and history of jaundice were all found not to be significant [24,30,39,100,101].…”
Section: Medical or Surgical Risk Factorsmentioning
confidence: 81%
“…Several other studies have reported higher prevalence among those dependent on blood and blood products, especially when compared with reports of a decline in seroprevalence [96][97][98][99][100][101]. In contrast to the above-mentioned findings, studies of HBV infection in pregnant women in Sudan, Yemen, and Mauritania have failed to show any evidence of blood transfusion being a risk factor for virus transmission [24,30,39]. This difference might be explained by better safety precautions being taken for blood donation, where screening for the virus is regularly undertaken.…”
Section: Factors Associated With Transmission Of Hbv Among Pregnant Wmentioning
confidence: 90%
See 2 more Smart Citations
“…In Mosul, Iraq, Shafiq [12] [2013] reported that genotype D is the predominant genotype in HBV acute and chronic infections. In addition, another study found that D genotype is the predominant among Mosul blood donors [11].In Arab countries the predominant genotype was D in Saudi Arabia [13], United Arab Emirates [14], Yemen [15], Lebanon [16], Jordan [17], Egypt [25], Libya [18] Mauritania [19], Morocco [20], and Syria [21].…”
Section: Disccussionmentioning
confidence: 99%